Acute fibrinous pleuropneumonia and septicaemia caused by Bibersteinia trehalosi in neonatal calves in New Zealand. Issue 1 (2nd January 2021) - Brown, SE; Bycroft, KA; Adam, K; Collett, MG
ABSTRACT: Case history: In July and August 2019, 15/40, ≤48-hour-old calves became acutely ill. The calves were all born on-farm, transferred to pens soon after birth, and fed with "gold" colostrum. The hygiene, biosecurity and ventilation in the pens were poor. Of the 15 calves, 11 died or were euthanised and four calves, ≤48-hour-old, that became acutely ill later in the outbreak were treated with cefquinome, a fourth-generation cephalosporin, and recovered. Clinical findings: The affected calves presented with acute recumbency, lethargy, tachypnoea, tachycardia, increased lung sounds, inability to stand or feed, and dehydration without pyrexia. Pathological findings: Gross findings in a calf that died naturally included fibrinous pleuropneumonia, marked oedematous expansion of the interlobular septa, especially in the ventral lung lobes, fibrinous polyserositis and fibrinous polyarthritis. A second calf that was euthanised had strikingly similar lung lesions. Histologically, the pulmonary interlobular septa of both calves were prominently expanded by oedema, dilated lymphatics and the infiltration of numerous neutrophils and macrophages interspersed with small Gram-negative rod bacteria. Likewise, the visceral pleura showed fibrinopurulent inflammation with numerous small Gram-negative rods. Microbiological findings: Microbial culture and matrix-assisted laser desorption ionisation time-of-flight (MALDI-TOF) mass spectrometry identified Bibersteinia trehalosi in the lung, stifle joint and peritoneal cavity of the first calf and lung of the second. Diagnosis: B. trehalosi acute fibrinous pleuropneumonia and septicaemia. Clinical relevance: This is the first report of the clinical findings and histological lesions of B. trehalosi pleuropneumonia and septicaemia in calves in New Zealand. The pathogen is isolated with increasing frequency from cases of bovine respiratory disease in dairy cows, feedlot cattle and calves in the United Kingdom and North America. The importance of microbial culture in cases such as this with unusual lung lesions in calves <48 hours of age, cannot be over emphasised. Cefquinome was administered to all remaining heifer calves and four calves that became ill later in the outbreak recovered after cefquinome treatment.